2018
DOI: 10.33366/japi.v3i1.839
|View full text |Cite
|
Sign up to set email alerts
|

Impelementasi pendididkan sex pada anak usia dini di sekolah

Abstract: Sex education in Indonesia is still a controversy, there are still many community members who have not agreed on sex education at home or at school. In general, the public view of sex education is considered "taboo" to talk about children, especially children of early age. the community often holds that it is not yet time for children of early age to understand about things related to sexuality. People assume that there is a time they will understand it naturally. that sex education from an early age is an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 0 publications
2
7
0
14
Order By: Relevance
“…In addition, AVA media has the benefit of being a tool to make it easier for mothers to remember or see the contents of messages contained in the video so that it can make it easier for mothers to give sex education to their children after the training. A previous study also found improved teacher skills after training on how to provide early sex education to children by using various game media that children like including dolls, puzzles, and singing (Haryono et al, 2018). Teachers and mothers are close people for preschool children because they interact daily with them.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…In addition, AVA media has the benefit of being a tool to make it easier for mothers to remember or see the contents of messages contained in the video so that it can make it easier for mothers to give sex education to their children after the training. A previous study also found improved teacher skills after training on how to provide early sex education to children by using various game media that children like including dolls, puzzles, and singing (Haryono et al, 2018). Teachers and mothers are close people for preschool children because they interact daily with them.…”
Section: Resultsmentioning
confidence: 92%
“…So that children are aware of the reproductive organs, both male and female, and understand how to care for them. In addition, other benefits can prevent children from various possible sexual crimes from irresponsible people and provide a sense of responsibility to the children about their sexuality (Haryono et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Berdasarkan hasil penelitian menunjukkan bahwa tingkat pengetahuan sebelum diberikan pendidikan kesehatan diketahui kurang baik dan tingkat pengetahuan setelah diberikan pendidikan kesehatan menggunakan media audio visual Widia Shofa Ilmiah,(AVA) sebagian besar ibu anak pra sekolah memiliki tingkat pengetahuan baik. Pendidikan kesehatan adalah sebuah proses pemberian informasi tentang kesehatan kepada masyarakat (Ilmiah et al, 2019) Media yang dapat digunakan dalam memberikan pendidikan kesehatan yaitu lagu, alat permainan seperti boneka, puzzle, permaninan pasir, filp chart, poster, video (Haryono et al, 2018). Faktor yang mempengaruhi keberhasilan pendidikan kesehatan yaitu ketepatan waktu, sasaran, materi menarik.…”
Section: Pembahasanunclassified